Health services research. (September 2018) - Warner, Ross M; Bastianpillai, Christopher; Lamb, Benjamin W; Sevdalis, Nick; Green, James SA
Health services research (HSR) is the science of the evaluation and improvement of health care provision. HSR can be used by health care organisations to develop and understand administrative, financial and organisational processes in order to improve efficacy of clinical treatments, efficiency of their delivery, and ultimately patient outcomes. HSR applies both quantitative and qualitative methodology, utilising data collected from real-life clinical practice, rather than the confines of more controlled traditional efficacy trials. With new and developing therapies, HSR provides an opportunity to enhance the delivery of cost-effective and efficient health care. Level of evidence: Not applicable (educational article).